PENGGUNAAN MEDIA QR CODE SEBAGAI ALAT BANTU PENILAIAN TENGAH SEMESTER (PTS) ILMU PENGETAHUAN ALAM DAN SOSIAL (IPAS) DI SEKOLAH DASAR NEGERI BANDA ACEH - Moulana, Mohammad Riefyal; Prastowo, Andi; Rahman, Fatur (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to analyze the implementation of QR Code media as an assessment tool in conducting the Mid-Semester Examination (PTS) for Science and Social Studies (IPAS) learning in Banda Aceh Public Elementary School, as well as to identify the supporting and inhibiting factors in its application. This research employed a descriptive qualitative method with a case study approach. The population consisted of 55 students from Grades V-A and V-B, with a sample of 24 students. Data were collected through direct observation, interviews with teachers and students, and documentation analysis related to the implementation of QR Codes in the PTS process. The data were analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The results indicate that the use of QR Codes in PTS improves the efficiency of question distribution and assessment processes, reduces paper usage, and enhances student motivation. Supporting factors include teacher and student readiness to use technology and time efficiency during the examination. However, challenges such as limited devices, unstable internet connections, and students’ adaptation difficulties were also found. To overcome these challenges, schools are advised to provide backup devices, improve network infrastructure, and conduct training for teachers and students. With optimal support, QR Codes have the potential to be applied in other learning evaluations in elementary education.